How Does Contemporary YA Literature Represent Rural People and Places? - Jennifer Sanders (University of Oklahoma Libraries, 2024)
This article presents a critical content analysis of representations of rural people and places in contemporary, middle grades and young adult novels. Interrogating representations is vital for implementing critical rural place pedagogies. Findings indicate this award-winning text set included diverse representations of racial, religious, and sexual identities. Characters often felt a sense of place-based belonging and identity but also experienced tensions of feeling stuck. Rural places were frequently depicted as places of despair and pervasive poverty, with a lack of middle or upper-middle income representations. Implications for teacher education are presented with suggestions for critical place pedagogies and developing counternarratives that convey the diversity of rural people and places.